2019
DOI: 10.1530/eje-19-0197
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with cortical bone loss and fractures in the elderly

Abstract: Introduction The role of vitamin D on bone microarchitecture and fragility is not clear. Objective To investigate whether vitamin D deficiency (25(OH)D <20 ng/mL) increases cortical bone loss and the severity of fractures. Design Cross-sectional study of 287 elderly women with at least one prevalent low-impact fracture. Methods Biochemistry, X-rays to identify vertebral fractures (VFs) and to confirm non-vertebral fractures (NonVFs), and high-resolution peripheral quantitative computed tomography (HR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
14
1
2
Order By: Relevance
“…This is in contrast to other studies that found only a significant proportion of vitamin D deficiency in older persons from 40 % to 65 %. 40,41 Vitamin D deficiency was found to be associated with several known geriatric syndromes as well as a strong association between vitamin D deficiency and increased risk of heart failure and cortical bone loss and fractures in the older person's oral, gastrointestinal, urinary, ocular, and respiratory infections. 40,42 The two main sources of vitamin D are the dietary and the endogenous synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to other studies that found only a significant proportion of vitamin D deficiency in older persons from 40 % to 65 %. 40,41 Vitamin D deficiency was found to be associated with several known geriatric syndromes as well as a strong association between vitamin D deficiency and increased risk of heart failure and cortical bone loss and fractures in the older person's oral, gastrointestinal, urinary, ocular, and respiratory infections. 40,42 The two main sources of vitamin D are the dietary and the endogenous synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…40,42 The two main sources of vitamin D are the dietary and the endogenous synthesis. 41 Vitamin D2 (ergocalciferol) is obtained from plants and a small quantity of vitamin D3 (cholecalciferol) is from animal-derived food, the main natural vitamin D source is skin synthesis during Early detection among older individuals with or without diabetes of frailty status is necessary for proper immediate nutritional and medical interventions. Studies have shown that a low protein diet resulted in a significant decline in muscle mass and strength in older women.…”
Section: Discussionmentioning
confidence: 99%
“…It ensures a good level of bone mineralization; in fact, vitamin D deficiency produces serious clinical consequences at the bone level that result in a reduction in bone mass and an increased risk of osteoporotic fractures, in particular of the femur [30][31][32]. Previous observational research has identified vitamin D deficiency as a risk factor for Acute Respiratory Distress Syndrome (ARDS) and ARDS severity [33], which can be a life-threatening complication of COVID-19.…”
Section: Recommendations At the Time Of Covid-19mentioning
confidence: 99%
“…EAAs cannot be synthesised endogenously and thus require exogenous supplementation. Amino acids and vitamins are used to prevent and treat exercise-induced fatigue, scurvy, rickets, beriberi disease, burns, and fractures [9][10][11][12][13][14], as well as malnutrition in pregnant or lactating women and in children [15,16]. EAAs are raw materials for sperm nucleic acid synthesis.…”
Section: Introductionmentioning
confidence: 99%